2020
DOI: 10.1186/s12886-019-1278-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytokine levels in the aqueous humor of polypoidal choroidal vasculopathy and neovascular age-related macular degeneration patients

Abstract: Background: The concentrations of cytokines in the aqueous humor from neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV) may vary. The study was conducted to compare various cytokine levels in the aqueous humor of eyes with PCV, nAMD and control. Methods: The present case control study included 49 treatment-naïve eyes from 49 patients (PCV 24, nAMD 11, and cataract 14 eyes). Totally 34 angiogenic and inflammatory cytokines in the aqueous humor were measured by Lumin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
(43 reference statements)
6
28
0
2
Order By: Relevance
“…The sensitivity analysis allowed us to determine the impact of individual outlier studies. There were multiple cytokines that would have been statistically significant if not for the results of a single study, such as that of IP‐10 with the recent study by Zhou et al (2020). This is related to both heterogeneity between studies and the small number of studies contributing to the analysis of some cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…The sensitivity analysis allowed us to determine the impact of individual outlier studies. There were multiple cytokines that would have been statistically significant if not for the results of a single study, such as that of IP‐10 with the recent study by Zhou et al (2020). This is related to both heterogeneity between studies and the small number of studies contributing to the analysis of some cytokines.…”
Section: Discussionmentioning
confidence: 96%
“…22,31 Also, elevation of complement activation products (complement factors Ba, H, I, C3a, 25,26 adhesion molecule-1, IL-6, IL-8, IP-10, C-reactive protein, angiopoietin-2, human growth factor, tissue inhibitor of metalloproteinases 1, C-X-C motif chemokines 12 and 13, tumor necrosis factor-α, IL-31, leukemia inhibitory factor, and stromal cell-derived factor-1-α. [7][8][9][10][11][12][13][14][15][16][32][33][34][35][36] A recent study that summarized these cytokine networks using cluster analysis suggested that VEGF and MCP-1 were key factors in the development of nAMD. 15 Although complement factors and angiogenic cytokines were associated with nAMD development, their relationships in the aqueous humor have not been fully determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokine levels in the aqueous humor can be useful for predicting treatment effects. 7,8 Among the cytokines mentioned above, VEGF [7][8][9][10][11][12][13][14][15][16] and MCP-1 7,8,10,15,16 have been considered key cytokines in the development of CNV. [17][18][19] The complement proteins are also important in CNV development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, IL-9 was previously involved in several AMD studies. IL-9 cytokine in the aqueous humor was measured, but differences between neovascular AMD and the control groups were not found [60]. IL-9 was also measured in aqueous humor samples of neovascular AMD before the treatment by intravitreal drug injection and after, and compared with the control group, but the statistical analysis did not show any differences between study groups [61].…”
mentioning
confidence: 96%